An introduction to sociolinguistics - Holmes, Janet, 1947-; Wilson, Nick (Sociolinguist) (Learning about language, 2022)
"Sociolinguistics is the study of the interaction between language and society. In this classic introductory work, Janet Holmes and Nick Wilson examine the role of language in a variety of social contexts, considering both how language works and how it can be used to signal and interpret various aspects of social identity. Divided into three sections, this book explains basic sociolinguistic concepts in the light of classic approaches as well as introducing more recent research. This sixth edition has been revised and updated throughout using key concepts and examples to guide the reader through this fascinating area, including: New material on gender; social media and online use of language; code-switching; and language policy An updated Companion Website that is fully cross-referenced within this book and featuring video and audio materials and links to useful websites. Revised examples and exercises that will include new material from Asia and South America Fully updated further reading and references sections. An Introduction to Sociolinguistics is an essential introductory text for all students of sociolinguistics and a splendid point of reference for students of English language studies, linguistics and applied linguistics"--